Travel time and travel cost in European air travel - Tamas Dusek (European Regional Science Association (ERSA), 2012)
The aim of the study is to examine two issues of consumer air travel accessibility in Europe, namely flight time and ticket costs. The first part of the paper discusses the various methodological problems of creating time matrix and cost matrix of air travel. Because of problems of conceptualizing of the air travel network and the modifiable areal unit problem the analysis is conducted on several spatial levels. The smallest network consists of 15 busiest airports and the largest network has 203 airports. Airports were selected based on the number of arriving and departing aircraft. The source of flight time data is the timetable for the non-stop flights. Flight time was calculated with a simple algorithm based on timetable flight time for one-stop and two-stop connections. The source of ticket cost data is an internet query of travel itineraries. Several distance matrices were created for different networks and date of flights. The applied part of analysis uses simple methods also, such as average flight time, speed, cost and unit cost. The deformation of time and cost space from the Euclidean space is analyzed by multidimensional scaling. The comparison of geographical space on one side, and time space and cost space on the other side is made by the simple regression analysis and bidimensional regression. Results show significant local and regional biases in time and cost space, relative to the air distance.
Keywords: 330